Analisis Pengaruh Atribut Produk, Harga, Bauran Promosi terhadap Motivasi dan Keputusan Pembelian (Studi pada Pelanggan Kartu Prabayar Telkomflexi–Trendy di Sawojajar, Kota Malang) - Djunaedi - (Jurnal Aplikasi Manajemen, 2011)
This study aims to describe the explanatory variables, namely: Attribute Product (X1=brand and X2=physical evidence), price (X3=product price), and Mix Promotions (X4=advertising, X5=sales promotion, X6=personal recommendation through word of mouth); variables between the motivation (X7=motivation purchase), and the dependent variable is Buying Decision (Y), and search and explain the influence of direct, indirect, and total effect of all three types of variable with 212 population were pre-paid card subscribers TelkomFlexi-Trendy in Sawojajar Housing Complex, Lesanpuro, Kedungkandang, Malang, 68 people were taken samples of respondents. It is analized by path analysis from SPSS for windows ver 11.5. The results based on descriptive analysis shows, in general, respondents gave very positive responses to the 8 variables studied. Based on inferential analysis showed that variables significantly X7 directly to the Y with the path coefficient (α) equal to 0.319. From these results found in the fact that the variables X1 which has a dominant influence with the total effect of 0.741.Keywords: Attribute Product, Price, Promotion Mix, Motivation, Decision to Purchase.